Syntheses, Crystal Structure and Magnetic Properties of an Unprecedented One‐Dimensional Coordination Polymer Derived from an {(NiL)2Ln} Node and a Pyrazine Spacer (H2L=N, N′‐Bis(salicylidene)‐1, 3‐propanediamine, Ln=Gd, Tb and Dy). Issue 11 (22nd July 2016) - Ghosh, Soumavo; Mahapatra, Prithwish; Kanetomo, Takuya; Drew, Michael G. B.; Ishida, Takayuki; Ghosh, Ashutosh
Abstract: In order to investigate the coordinative interaction of the [Ni II L] metalloligand with lanthanides (H2 L = N, N ′‐bis(salicylidene)‐1, 3‐propanediamine or H2 salpn) and the building block potential of the resultant unstable {(Ni II L)2 Ln III } (Ln III =Lanthanides) complex with a short spacer pyrazine (pyz), three heterometallic coordination polymers of formulae [{(NiL)2 Ln(NO3 )3 }pyz]n ⋅1.5nH2 O [Ln=Gd (1 ), Tb (2 ) and Dy (3 )] have been synthesized. In these compounds the central Ln III ion is connected to two terminal [NiL] metalloligands through µ1, 1 ‐diphenoxido bridges to form the trinuclear node with three nitrato coligands (LnO9 monocapped square‐antiprism). The coordinative preference of pyrazine ligand towards the Ni II ‐centre of the trinuclear units leads to the formation of these tailored 1D‐zigzag coordination polymers with transoid trinuclear nodes. The magnetization at 1.8 K for1 (10.4 μ B at 7 T) indicates the presence of Gd−Ni ferromagnetic coupling through the phenoxido bridges. The exchange parameter was determined to be +0.179(4) K from the magnetic susceptibility measurement. Both in‐phase and out‐of‐phase ac magnetic measurements under an applied dc magnetic field reveal temperature dependence of the susceptibility at different frequencies below 5 K for compound3, characteristic of single molecule magnets (SMMs) or polymeric aggregates of SMMs. Abstract : Rationally designed connectivity between bimetallic trinuclear nodes has been made from transoid ‐[(Ni II L)2 Ln III ] 3+ tecton (Ln=Gd, Tb, Dy) and pyrazine spacer which form tailored 1D‐zigzag coordination polymer. The Gd−Ni ferromagnetic coupling is confirmed. The Ni2 Dy compound shows characteristic of SMMs or polymeric aggregates of SMMs under an applied dc field.